2022
DOI: 10.3389/feduc.2022.853303
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence Scale for International Students: A Proposal for a Developed Version

Abstract: In higher education, making international students aware of their EI could improve emotional awareness, adaptability, and functioning, thereby assisting in day-to-day interactions and adapting to life in a foreign country. Incorporating an Emotional Intelligence Scale (EIS) could aid in the on boarding of international students. This study aimed to develop and validate an EIS capable of accurately measuring EI amongst international students attending a teaching university in Northwest China. The sample consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 40 publications
3
9
1
Order By: Relevance
“…There is conclusive evidence that the BST is significant (X 2 = 33476.905, df = 703, p < 0.001). As the KMO value is more than 0.60, these findings confirmed the instrument's suitability for factor analysis [48][49][50]. With this data set, six variables seem to be the most likely choice.…”
Section: The Research Instrumentsupporting
confidence: 66%
See 1 more Smart Citation
“…There is conclusive evidence that the BST is significant (X 2 = 33476.905, df = 703, p < 0.001). As the KMO value is more than 0.60, these findings confirmed the instrument's suitability for factor analysis [48][49][50]. With this data set, six variables seem to be the most likely choice.…”
Section: The Research Instrumentsupporting
confidence: 66%
“…In addition, the factorial validity of the study instrument was examined. This research yielded a higher KMO value (0.955) than has been previously reported in the literature [49,50]. Data with multiple variables were normally distributed, as shown by the significance of the Chi-square statistics obtained at the end of the BST.…”
Section: The Research Instrumentsupporting
confidence: 48%
“…Kaiser ( 1974 ) indicated that factor analysis should be carried out when the KMO value was more than 0.40 (Watkins, 2017 ), while Field ( 2009 ) implied KMO values above 0.60 to be acceptable. Table 2 illustrates the EFA, and all the AE tool items were loaded higher than 0.40 and considered good value (Blaikie, 2004 ; Al-Qadri et al, 2022 ). That suggested the factor item load should be at least 0.40.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to Al-Qadri et al (2022), Eschenbacher (2022), Fang and Huang (2022), Finch and Finch (2022), Galos (2022), Holliman et al (2022), andWesterveen et al (2022), it has been proved that the approach to state regulation of educational and labor migration in conditions of economic integration (as opposed to the approach in the individual economic growth of countries) should involve stimulating social mobility and creating social (educational and labor) elevators rather than retention of personnel. Artificial retention of human resources in the country leads to their degradation and unemployment, while the creation of a single education market and the labor market in the integration association of countries (as in the successful example of the EAEU) makes it possible to free the flow of human resources and most effectively manage them in full economic freedom in support of the implementation of social investment model of economic growth.…”
Section: Discussionmentioning
confidence: 99%
“…State management of educational migration in the knowledge economy in implementing the social investment model of economic growth is carried out according to the same principle (Holliman et al, 2022). In international university rankings, including QS and THE, the presence of international students and professors is considered a competitive advantage for universities (Al-Qadri et al, 2022).…”
Section: Underpinning Theorymentioning
confidence: 99%